Biomarcadores endoteliais em pacientes críticos com Covid-19: potenciais preditores da necessidade de diálise e prognóstico - Saranza, Marza de Sousa (2023)
Introduction: Acute kidney injury in patients admitted to the ICU due to COVID-19 has an important impact on the prognosis of this population and endothelial dysfunction is at the heart of the pathophysiology of kidney injury. Patients requiring dialysis have high mortality rates and studies are needed to develop better strategies for early identification of these individuals. Aim: To describe the clinical and laboratory characteristics of patients with COVID-19 who required dialysis during ICU stay, evaluate the performance of endothelial biomarkers to predict the need for dialysis and prognosis of this population. Methods: This is a prospective study with 58 unvaccinated COVID-19 patients admitted to the ICU. Biochemical tests and the vascular biomarkers VCAM-1, Syndecan-1, Angiopoietin-1 and Angiopoeitin-2 were analyzed. The severity of patients admitted to the ICU was estimated using the SAPS3 score and all ICU data were calculated from the EpimedTM ® System. Data were analyzed using SPSS software for Macintosh, version 23 (Armonk, NY: IBM Corp.). A value of p<0.05 was considered statistically significant for all analytical tests. Results: Among the 58 patients in the study, 37 (63.79%) developed the need for dialysis during their stay in the ICU. These patients were older (62.4 ± 12.5 vs. 53.5 ± 16.5 years, p=0.037) and had a higher prevalence of AKI (95% vs. 39%, p<0.001). The dialysis group used more vasopressors (70% vs. 26%, p=0.001) and mechanical ventilation (95% vs. 69%, p=0.022) and had a higher mortality rate compared to the group that did not undergo dialysis (76.2% vs.23.8%, p<0.001). SAPS3 was higher in patients who required dialysis (63 ± 13.8 vs. 49.5 ± 14.2, p<0.001) and they had lower platelet levels and higher LDH, urea and creatinine levels. VCAM-1 and the Ang-2/Ang-1 ratio were increased in the group that required dialysis. The Ang-2/Ang-1 ratio had better AUC-ROC (0.684 –95%CI: 0.536 to 0.833; p=0.022), followed by VCAM-1 (0.673 –95%CI: 0.521 to 0.826; p=0.031) . In a combined approach using VCAM-1 and Syndecan-1 levels and Ang-2/Ang-1 ratio, AUC-ROC improved to 0.713 –95%CI: 0.568 to 0.858; p=0.008. Patients with levels above the cutoff levels of syndecan-1, VCAM-1 and Ang-2/Ang-1 ratio required dialysis earlier. Older age, use of vasopressors, higher SAPS3 score, LDH, VCAM-1, Syndecan-1 levels, Ang-2/Ang-1 ratio and decreased platelet levels contributed to the need for dialysis (hazard ratio > 1 ,00). Conclusion: Unvaccinated patients with critical forms of COVID-19 who required dialysis during ICU stay were older, had a greater need for vasopressors and mechanical ventilation upon admission to the ICU, had a higher SAPS3 score and had higher mortality. Levels of endothelial biomarkers above the cutoff point determined in the study were associated with higher mortality and faster progression of kidney injury until the start of hemodialysis. VCAM-1 and Ang-2/Ang-1 ratio demonstrated a good performance in predicting the need for dialysis and the combined analysis of these two markers, together with Syndecan-1 levels, showed an even better performance.